Clinical and histopathological evidence of oral squamous cell carcinoma in young patients: systematized review - Janaina Almeida Mesquita; Alessandro Leite Cavalvanti; Cassiano Francisco Weege Nonaka; Gustavo Pina Godoy; Pollianna Muniz Alves (Sociedade Brasileira de Patologia Clínica, 2014)
The oral squamous cell carcinoma (OSCC) very often affects subjects above the sixth decade of life. However an increasing incidence has been observed in younger individuals, below 40 years. We conducted a systematized review of the current clinical, histopathological and therapeutic aspects of OSCC in young patients. Our work included studies that addressed OSCC involving young patients in the period 2007 2012, and which were indexed in PubMed. Initially, 499 articles were obtained; after refinement, 340 articles had their titles and abstracts evaluated, with 17 included in the sample. The majority of studies reported male predominance (87.5%), association with tobacco and/ or alcohol use (66.6%), advanced clinical stages at diagnosis (77.7%) and, at histopathology, moderately differentiated tumors (72.7%). Based on the results, we believe there are differences in the factors associated with pathogenesis, biological behavior and prognosis in young patients, since most studies show more rapid and aggressive tumor progression in this age group. We suggest the conduction of research focusing on the pathogenesis and carcinogenesis of OSCC in young patients, thereby searching for better scientific evidence.